Blue Photoluminescence of Au Nanoclusters Synthesized Using Dendrimer Templates under Mild Conditions. (11th September 2018) - Kim, Jun Myung; Shim, Hyeong Seop; Kwon, Jihye; Kim, Hai Dong; Song, Jae Kyu; Kim, Joohoon
Abstract :